Organic Reactions 2011
DOI: 10.1002/0471264180.or001.01
|View full text |Cite
|
Sign up to set email alerts
|

The R eformatsky Reaction

Abstract: The reaction which takes place between a carbonyl compound such as an aldehyde, ketone, or an ester, and an alpha‐haloester in the presence of zinc is commonly known as the Reformatsky reaction. It represents an extension of the reactions of carbonyl compounds with a dialkylzinc or an alkylzinc halide, but possesses the advantage that the isolation of the organozinc compound is unnecessary. The process creates a new carbon‐carbon linkage and involves the following: Formation of an organozinc halide; addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…It was clearly observed that the composite was in nanodimension size (about 48 nm). Chemically, coumarins can be synthesized by a range of methods such as the Perkin, Pechmann reaction, Knoevenagel condensation, Reformatsky, Wittig, and catalytic cyclization reactions [21][22][23][24][25][26][27][28][29]. Acid catalyzed Pechmann reaction is the simple and normally used method for synthesizing coumarins from activated phenols, mainly metasubstituted phenols containing nucleophilic substituent at meta-position.…”
Section: Resultsmentioning
confidence: 99%
“…It was clearly observed that the composite was in nanodimension size (about 48 nm). Chemically, coumarins can be synthesized by a range of methods such as the Perkin, Pechmann reaction, Knoevenagel condensation, Reformatsky, Wittig, and catalytic cyclization reactions [21][22][23][24][25][26][27][28][29]. Acid catalyzed Pechmann reaction is the simple and normally used method for synthesizing coumarins from activated phenols, mainly metasubstituted phenols containing nucleophilic substituent at meta-position.…”
Section: Resultsmentioning
confidence: 99%
“…Coumarins have been synthesized by several methods including Pechmann [6], Perkin [7], Knoevenegal [8], Reformatsky [9] and Wittig reactions [10]. However, the Pechmann reaction is the most widely applied for the synthesis of coumarins due to simple reaction conditions and good yields.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins were first synthesized via the Perkin reaction, and many simple coumarins are still prepared through this method, the Knoevemagel reaction emerged as an important synthetic method to synthesized coumarin derivatives with carboxyl group at the 3-position [12,13]. Many other synthetic methods for coumarins have been reported, including the Pechmann [14], Reformatsky [15] and Witting reactions [16]. The review is not exhaustive, it is intended to acquaint the reader with interesting group of synthetic organic compounds.…”
Section: Introductionmentioning
confidence: 99%